Human Trafficking, A Shadow of Migration – Evidence from Germany. - Cho, Seo-Young (Journal of Development Studies, 2015)
This paper investigates relationship between migration and human trafficking in Germany by analyzing macro-level data from 150 countries. The empirical results suggest that migrant networks of a specific source country pull human trafficking from that respective country. However, the migration effect varies across different income levels of source countries. The positive effect of migration on human trafficking decreases as income increases, and furthermore, the effect is irrelevant to high income countries. In addition, the migration effect is particularly significant on the criminalisation side of human trafficking, but the evidence is less clear when it concerns the victimisation side.